Observation of an intriguing equatorial plasma bubble event over Indian sector - Ghodpage, R.N.; Gurav, O. B.; Taori, A.; Sau, S.; Patil, P.T.; Erram, V.C.; Sripathi, S. (My University, 2021)
We report an interesting Equatorial Plasma Bubbles (EPBs) event during the night of March 22–23, 2017. To investigate the dynamics of observed EPBs, we utilize multi-instrument data obtained with all-sky imager (ASI) from Panhala (16.48°N, 74.6°E, 11.1°N Dip. Lat.), Canadian Advanced Digital Ionosonde (CADI) from Tirunelveli (8.73°N, 77.7°E, 1.6°N Dip. Lat.) and ionospheric backscatter echoes data of Gadanki Ionospheric Radar Interferometer (GIRI) radar from Gadanki (13.5°N, 79.2°E, 6.5°N Dip. Lat.) over Indian regions. The optical observations from Panhala reveal clear signatures of EPBs from ∼1600 UT onwards and corresponding ESF occurrence is noted in CADI at Tirunelveli as well. Backscatter echoes are also recorded in Range time intensity map obtained by GIRI after ∼17:45 UT. On this night, two EPBs (EPB1 and EPB2) are observed with inter-depletion distance of ∼600 km. The EPB1 drifts eastward throughout the night and evolves with time as bifurcated structures while the trailing EPB2 drifts eastward initially and eventually drifts westward. We believe that this is the first evidence of differential drifts of EPBs imaged through ASI over a narrow longitudinal zone over the Indian region.
Keywords: Equatorial Plasma Bubble, EPB, Indian sector